(untitled) (Aintelia Science Notes, 2024)
The integration of autonomous mobile robots (Agri-Robots) is critical for addressing global food security challenges and increasing efficiency in precision agriculture (PA). The operational efficacy of these robots, which perform tasks from planting to harvesting, hinges entirely on robust, high-speed, and low-latency wireless communication. This review analyzes the performance trade-offs among short-range (Wi-Fi, Bluetooth, Zigbee) and wide-area (LoRaWAN, 4G, 5G-SA) technologies, classifying their suitability based on key metrics: Massive Machine-Type Communications (mMTC) for sensing, Ultra-Reliable Low-Latency Communication (URLLC) for control, and Enhanced Mobile Broadband (eMBB) for data offload. Findings indicate that a single standard is insufficient; LoRaWAN excels in long-range, low-power sensing, while private 5G-SA is mandatory for safety-critical, low-latency control. Operational success is inhibited by environmental factors, such as vegetation-induced signal attenuation and systemic issues, including market fragmentation and proprietary data ecosystems. The critical pathway forward involves adopting hybrid network architectures that intelligently combine Low-Earth Orbit (LEO) satellite services for ubiquitous geographic coverage with terrestrial 5G/Wi-Fi for high-throughput edge computing. Further advancements depend on the development of AI-driven autonomous network management and the adoption of lightweight application protocols like CoAP.